IMMUNODIAGNOSIS OF PULMONARY AND EXTRAPULMONARY TUBERCULOSIS USING MYCOBACTERIUM TUBERCULOSIS ES-31/41 ANTIGEN - DR. MOHAMMED SABIULLAH; DR. S. LAXMI NARAYANA; DR. J. MADHAVILATHA; DR. M. GOURI DEVI; DR. V. RATNA KUMARI; DR. RAHMATHUNNISA; DR. R. BABU RAO (International Journal of Pharma and Bio Sciences, 2015)
Tuberculosis is still a major health problem in India and most developing countries and its incidence is rising in many developed countries. This resurgence has been attributed to the HIV epidemic and WHO has declared TB as a global health emergency in 1993. Immunodiagnosis has an important role in screening, diagnosis and management of Tuberculosis. In the present study we have analysed the diagnostic potential for detection of IgG antibody against ES-31/41 antigen by indirect penicillinase ELISA in the clinically and bacteriologically confirmed pulmonary and extrapulmonary tuberculosis cases to determine the usefulness of immunoglobulin in the diagnosis of patients attending the hospital. 47 (90.38%) out of 52 pulmonary tuberculosis cases (clinically diagnosed and/or AFB-positive), 33 (80.48%) out of 41 extrapulmonary tuberculosis cases, only one out of 10 (10%) of healthy group and only four out of 25 (16.0%) disease control cases were positive for IgG antibody to Mycobacterium tuberculosis ES antigen. In the present study, a sensitivity of 90.38% and 80.48% for IgG antibody detection was achieved in the pulmonary and extrapulmonary tuberculosis respectively. Hence, the study demonstrated the potential of this assay in the diagnosis of pulmonary and extrapulmonary tuberculosis.